Comparison of Allograft and Bovine Xenograft in Calcaneal Lengthening Osteotomy for Flatfoot Deformity in Cerebral Palsy. Issue 3 (April 2017) - Rhodes, Jason; Mansour, Alfred; Frickman, Allison; Pritchard, Breanna; Flynn, Katherine; Pan, Zhaoxing; Chang, Frank; Miller, Nancy
Abstract : Background: The Evan's calcaneal lengthening osteotomy is a treatment method for spastic flatfoot deformity in patients with cerebral palsy that fail nonoperative measures. Autograft and allograft have been reported as potential graft choices. Bovine xenograft has been introduced as an alternative, but limited human data exists supporting its efficacy. This study compares the long-term results of allograft versus xenograft in isolated Evan's procedure performed for correction of flexible spastic flatfoot deformity. Methods: This retrospective study accessed charts of 4- to 18-year-olds diagnosed with cerebral palsy who received an Evan's procedure. Preoperative and postoperative radiographic measurements (lateral calcaneal pitch, lateral talocalcaneal, lateral talo-first metatarsal, anteroposterior talonavicular coverage, anteroposterior talo-first metatarsal), graft incorporation, recurrence, secondary procedures, and complications were recorded and analyzed between graft types. Results: Sixty-three feet (34 allograft and 29 xenograft) in 36 patients (mean age 9.3 y) were included. Gross Motor Function Classification System between groups was significant ( P =0.001). Mean time for preoperative x-rays was 5.3 months before day of surgery (DOS) for allograft and 3.6 months for xenograft. Mean time of first and last postoperative x-ray for allograft was 3.6 and 39.5 months, respectively; for xenograft, 1.8 and 35.1 months, respectively. There was a significant difference in timing of preoperative x-ray to DOS and DOS to first postoperative x-ray ( P =0.012, 0.006, respectively). Radiographically, xenograft retained postoperative improvement better than allograft, yet allograft had a higher grade 4 incorporation rate ( P =0.036). The allograft group experienced significantly more cast pressure ulcers ( P =0.006), but no other differences in complications between groups, and no infections were reported in either group. Conclusions: Allograft incorporated better than xenograft, likely with a greater potential to reach grade 5 incorporation, yet both groups retained postoperative improvement. Results indicate both grafts are appropriate; yet incorporation rate could affect correction maintenance, and should be considered during graft selection for Evan's procedure. Level of Evidence: This study presents clinical results using a novel bone graft material. Level III—retrospective comparative study.